Indonesian vocational college students’ attitudes towards project-based learning in English courses - Mutiaraningrum, Ira; Fitriati, Sri Wuli; Yuliasri, Issy; Saleh, Mursid (Institute of Advanced Engineering and Science, 2024)
Following the mandatory adoption of project-based learning (PjBL) in Indonesian vocational education, there has been a revival in popularity as a prevalent instructional approach in higher education. However, no research on students' attitudes toward mandatory PjBL in Indonesia has raised concerns about its acceptance. This article describes Indonesian vocational college students’ attitudes toward PjBL in English language courses. The study specifically focuses on cognitive, affective, and behavioral attitudes and how students perceive the advantages of PjBL for their English skills and career aspirations. This quantitative study included 336 Indonesian vocational students from twelve state and private colleges in Indonesia. The results of this study revealed that students had a positive attitude toward PjBL in their English courses. Students’ cognitive, affective, and behavioral attitudes indirectly influenced their career aspirations, with English skill benefits acting as mediators. This study proves that how students feel, think, and behave affects their future career goals by shaping how they perceive improvement in their English language skills.